Services in the European Single Market and in World Trade: Country Implementation Barriers - Mylonakis, John (Journal of Public Administration and Governance, 2023)
The Services sector has been the backbone of the global economy and the most dynamic player in international trade. Trade in Services helps to develop countries’ economies, increases competition, and promotes the personal skills of employees. The European Single Market is a cornerstone of the European Union, being the single space within which economic growth factors move freely and unhindered. The scope of this paper is to connect these social and economic factors and to show on the one hand the expected benefits from a single market and on the other the chaotic difficulties emerging from its implementation in many member countries. The Covid-19 pandemic highlighted weaknesses in the functioning of the European Single Market. It is worth mentioning the fact that the Services Directive is the most important step towards achieving a Single Market as it ensures that both service providers and recipients of services can more easily benefit from fundamental freedoms of the European Union, such as freedom of establishment and freedom to provide services to cross-border level.